Tenotomia do músculo flexor digital superficial e desmotomia acessória em equinos: goniometria radiometacarpiana, metacarpofalângica e interfalângica - Hussni, Carlos Alberto [UNESP] (2010)
The purpose of this study was to investigate the effects of the superficial digital tenotomy and the superior check ligament desmotomy on the radio-metacarpal, metacarpophalangeal, proximal and distal interphalangeal angles in horses. Under general anesthesia the superficial digital flexor tenotomy and superior check ligament desmotomy were performed, respectively, on the right and left forelimbs in nine horses. Before surgery and on 15th, 30th, and 60th postoperative days the radio-metacarpal, metacarpophalangeal, and proximal and distal interphalangeal angles were measured by radiographic examination. Tenotomy decreased significantly the metacarpophalangeal angle (mean ± standard deviation: preoperative – 140.7º ± 6.85; 60th day – 128.2º ± 5.93) and increased the distal interphalangeal angle (mean ± standard deviation: preoperative – 172.6 ± 1.87; 60th day – 167.6 ± 1.36). Desmotomy decreased the proximal interphalangeal angle (mean ± standard deviation: preoperative – 180.2º ± 5.43; 60th day- 197.3º ± 8.29). These surgical procedures did not change the radio-metacarpal angle. The superficial digital flexor tenotomy and the superior check ligament desmotomy cause different and significant changes in joint angles distal to the carpus.